Intraparenchymal haemorrhage and uncal herniation resulting from dobutamine stress echocardiography. (18th March 2014) - Bennin, Charles-Lwanga Kobina; Ramoutar, Virin; Velarde, Gladys
Abstract : Intracranial haemorrhage (ICH) resulting from dobutamine stress echocardiography (DSE) is a rare complication in an otherwise relatively safe procedure. There has been one previously reported case of ICH associated with DSE in a patient who was fully anticoagulated. The authors report a second case of ICH associated with DSE leading to a poor outcome. Unlike the previous report, this patient was not fully anticoagulated and bleeding resulted from uncontrolled hypertension. Clinicians should be attentive to the risk of ICH associated with DSE in the setting of uncontrolled hypertension.